Testing The Effect Of Debt To Equity Ratio And Dividend Payout Ratio On Stock Return In The Food Industry And Beverages - Deni Sunaryo; Etty Puji Lestari; Siti Puryandani; Hersugondo (Universitas Serang Raya, 2023)
This study aims to determine the effect of Debt to Equity Ratio on stock returns, dividend policy on stock returns in Manufacturing Companies Food Sub Sector, And Beverages Listed on the Indonesia Stock Exchange Period 20 17 -20 20. Investors invest in a company to get a return. Before investing, investors need to pay attention to the company's financial performance. The main information needed by investors is accounting information needed to assess investment risk and estimate the rate of return on investment. This research was conducted using quantitative methods. There were 30 companies in this research and 18 companies were taken as a sample using the purposive sampling method—data analysis using SPSS version 25. Based on the partial results of the study, it shows that the Debt to Equity Ratio variable does not affect stock returns. While the dividend policy variable influences stock returns. Meanwhile, based on the simultaneous results, the Debt to Equity Ratio and Dividend Payout Ratio simultaneously affect stock returns. For further research, it is recommended to conduct similar research, which is expected to be able to add or replace other variables besides the variables used in this study with other factors that might influence stock returns such as return on assets (ROA), company size, etc.